The Identity and Distribution of Certain Taxa in Bihar and Orissa - Pal, D. C. (Indian Forester, 1971)
The identity and distribution of three grass species name1y Brachiaria miliiformis (Presl) A. Chase, Digitaria preslii (Kunth) Henr. and Trachys muricata (L.) Pers. Are discussed.